Task assignment and scheduling in a constrained manufacturing system using GA. (18th July 2008) - Choudhury, B.B.; Mishra, D.; Biswal, B.B.
Driven by open global competition and rapidly changing technology, manufacturing organisations come across continuous change and significant amount of uncertainty. With increasing trend in customers' demand for a greater variety, high quality and competitive cost, traditional manufacturing approaches face threats to remain competitive. Flexible Manufacturing Systems (FMS) have brought in significant benefits to manufacturing sectors. The ability of FMS to flex to both internal and external changes gives rise to improvement in throughput, product quality, information flows, reliability and other strategic advantages. However, the constraints with the individual candidates of FMS must be considered while assigning tasks and making schedules. This makes the scheduling problem complex. Appropriate scheduling methodology can reap better results. In the present work, Genetic Algorithm (GA) is utilised for optimisation of scheduling of FMS. This approach is used to determine the best available combination of resources for processing the product and the method has been shown through a suitable example.